Um estudo da performance da oralidade no cinema: Registros da voz na linguagem documental. - Doppenschmitt, Elen Cristina Souza (2005)
The present work studies the importance of the voice in documentary movies, considering this as a privileged space where we can observe and analyze the performances of the voice, and in this way to contribute for the study of the orality in the medias. The choice of the documentary film "Adão ou Somos Todos Filhos da Terra" by Walter Salles and Daniella Thomas for the proposed analysis, is mainly due to the fact that this film (through the use of you speeches, carols, poems) shows the changes between the record and the practices of the orality, as well as the vehiculation of speeches and verbal systems which are present in the visual movie complex. Using the concepts of orality and performance studied by Paul Zumthor, allows us to analyze our documentary film looking for an understanding of the dialogue that is established between the visual and oral system, from a voice that is no longer a presence, but a presence captured by the film. The possible interpretations about the performances of the voice show, in this way, his importance in the construction of narrativities for the documentary movies. The acurate study of the orality in the and of the documentary movies is justified by the employment of certain aesthetic mechanisms used by directors when telling their stories. The absolute presence of the narrator-cinéaste is diluted in photography and editing process, ending by bringing him melted in his own cast. The figure of the personage as a narrador in oral process enables the understanding of the mixture of present voices (cinéaste, personages, immemorial oralities and so on), which make us to believe that we faced a multiple narratives in which it is possible to enrich the point of view about the themes treated. Also show the border zones between the documentary and the fiction, between sound and image, as well as between movies and the culture to expose some hybridization processes that provide a new comprehension in the understanding of the movie narrative, showing that the making of the documental text modifies:"Adão ou Somos Todos Filhos da Terra" is prone to an analysis in what it is possible to verify how the documentary becomes free from the truth-model understood as the one that it constitutes when finding in the fable-function a new possibility of aesthetics of the real . Finally it is important to understand how one can, through the voice and its performances, to have access to a conscience of the cultural differences and the existence of the other. The documentary is, in this way, capable of making the cultural memory to become more accessible, through one voice, even when that is captured by the media.